Autoimmune polyendocrine syndrome type 1 a case report from Bangladesh - Haq, Tahniyah; Rahman, Anisur; Ikhtaire, Shapur (IMC Journal of Medical Science, 2017)
We describe a case of a 26 years old man who presented with adrenocortical insufficiency followed by hypoparathyroidism and subsequently mucocutaneous candidiasis. He also had nail dystrophy, cataract and alopecia, but no other endocrinopathies. He was diagnosed as a case of autoimmune polyendocrine syndrome type 1(APS 1). APS1 is a rare endocrine disorder and only a few cases have been reported from Bangladesh.